White light single-shot interferometry with colour CCD camera for optical inspection of microsystems - Upputuri, Paul Kumar (2015)
White light interferometry is a well-established optical tool for surface metrology of reflective samples. In this work, we discuss a single-shot white light interferometer based on single-chip color CCD camera and Hilbert transformation. The approach makes the measurement dynamic, faster, easier and cost-effective for industrial applications. Here we acquire only one white light interferogram using colour CCD camera and then decompose into its individual components using software. We present a simple Hilbert transformation approach to remove the non-uniform bias associated with the interference signal. The phases at individual wavelengths are calculated using Hilbert transformation. The use of Hilbert transformation introduces phase error which depends on number of fringe cycles. We discuss these errors. Experimental results on reflective micro-scale-samples for surface profiling are presented.